Alternating irrigation water quality as a method to control solute concentrations and mass fluxes below irrigated fields: A numerical study. Issue 5 (7th May 2016) - Russo, David
Abstract: The aim of the present numerical study was to extend the data‐driven protocol for the control of soil salinity, to control chloride and nitrate concentrations and mass fluxes below agricultural fields irrigated with treated waste water (TWW). The protocol is based on alternating irrigation water quality between TWW and desalinized water (DSW), guided by solute concentrations at soil depth, zs . Two different schemes, the first requires measurements of soil solution concentrations of chloride and nitrate at zs, while, the second scheme requires only measurements of soil solution EC at zs, were investigated. For this purpose, 3‐D numerical simulations of flow and transport were performed for variably saturated, spatially heterogeneous, flow domains located at two different field sites. The sites differ in crop type, irrigation method, and in their lithology; these differences, in turn, considerably affect the performance of the proposed schemes, expressed in terms of their ability to reduce solute concentrations that drained below the root zone. Results of the analyses suggest that the proposed data‐driven schemes allow the use of low‐quality water for irrigation, while minimizing the consumption of high‐quality water to a level, which, for given climate, soil, crop, irrigation method, and water quality, may be determined by the allowable nitrate and chloride concentrations in the groundwater. The results of the present study indicate that with respect to the diminution of groundwater contamination by chloride and nitrate, the more data demanding, first scheme is superior the second scheme. Key Points: A new protocol to control solute fluxes below the root zone is presented The protocol may considerably improve groundwater quality The protocol performance is soil, crop, and irrigation method dependent